Striking home: ideal-type of terrorism - Aran, Gideon (Terrorism and political violence, 2019)
This essay presents some preliminary notes in an anthropological perspective on terrorism. The following aims to be a questioning review of issues that haunt informed students of terrorism, and yet also an introductory text to the study of terrorism. It is revisionist but didactic. The essay is based on extended research of Palestinian and Israeli terrorism cases, and on critical integration of the literature on terrorism. It offers an alternative approach to the problem of the definition and distinct character of terrorism, expands on overlooked aspects of terrorism, like its relationship to the concept of “home,” emphasizes under-theorized subjects, like the randomness of the targets, and discusses hitherto untouched topics, like the “bad death” of terrorism’s victims. Terrorism is examined in terms of liminality and hybridity, and consequently as more subversive than coercive, threatening our ontological security no less than our physical security.